Analysis of Custodial Deaths in New Delhi: A 13 Years Study - Jhamad, Akhilesh R; Sikary, Asit Kumar; Millo , T (Journal of Indian Academy of Forensic Medicine, 2014)
Custody related deaths are not uncommon in India. A meticulous autopsy becomes a necessary part of the investigation. A retrospective study was done to analyze the prevalence and demographic pattern of custodial related deaths, whose autopsy were conducted at AIIMS, New Delhi. The autopsy reports of 13 years (1999-2011) were analyzed retrospectively. There were total 15 cases of custodial related deaths. All cases were male and majority was in the age group of 25-35 years (8 cases). 9 cases belonged to Hindu and 6 cases belong to Muslim. 10 cases died due to natural disease and 3 cases due to unnatural causes. 10 cases died in the hospital and 5 cases in the custody. Among the 3 unnatural deaths 1 died due to hanging, 1 due to fall from height and 1 from blunt injuries. In 2 cases no exact cause of death could be determined. In India there is overcrowding of prisoners in the jail. In spite of medical screening of the prisoners the infectious diseases like TB is very prevalent in jails. The national human rights commission is taking up the issues to improve the jail conditions in India.